Studies on the Nature and Pattern of Distribution of Tension Wood in Hevea brasiliensis Muell. Arg. (Rubber Wood) - Vijenora Rao, H.; Dayal, R.; Sharma, Babulal (Indian Forester, 1983)
The nature and pattern of distribution of tension wood in rubber wood (Hevea brasiliensis Muell Arg.) has been studied. The studies indicate that tension wood in this species can best be recognized under the microscope only. It has been found to occur both as diffuse and in bands. Staining reactions indicate that it is the S3 (G) layer which is gelatinised and non-lignified. Further, the proportion of tension wood has been found to vary in different planks representing different trees and also along the length within the planks. This erratic distribution of tension wood may be responsible for causing warping of the match splints.